2000
DOI: 10.1063/1.1289273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of transition-metal gettering in silicon

Abstract: The atomic process, kinetics, and equilibrium thermodynamics underlying the gettering of transition-metal impurities in Si are reviewed. Methods for mathematical modeling of gettering are discussed and illustrated. Needs for further research are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
174
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 272 publications
(186 citation statements)
references
References 132 publications
5
174
1
6
Order By: Relevance
“…Following implantation of Si samples with various heavy ions it was also observed that Fe and other transition metals such as Cu preferentially decorate two regions in the implanted sample: the end of range of the implanted ions, the so-called Rp-region, and midway between the projected range and the surface, the so-called Rp / 2-region. [4][5][6][7][8] It has been suggested that vacancy-type defects at half of the projected range act as effective gettering sites for Fe in the Rp /2 region. 8 We have therefore also undertaken simulations for shallower depth profiles of Fe, centered at half of the 60 keV implantation depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following implantation of Si samples with various heavy ions it was also observed that Fe and other transition metals such as Cu preferentially decorate two regions in the implanted sample: the end of range of the implanted ions, the so-called Rp-region, and midway between the projected range and the surface, the so-called Rp / 2-region. [4][5][6][7][8] It has been suggested that vacancy-type defects at half of the projected range act as effective gettering sites for Fe in the Rp /2 region. 8 We have therefore also undertaken simulations for shallower depth profiles of Fe, centered at half of the 60 keV implantation depth.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Hence one might expect that the lattice sites following high-temperature annealing represent Fe within small silicide precipitates and the formation of the precipitates to depend on the Fe concentration of the samples. It is therefore very surprising that no correlation of the various Fe lattice sites with the implanted fluence was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, 3d-transition metals in Si have been in the focus of silicon research due to their unwanted presence as contaminants [1][2][3][4][5] . Depending on the complexes that the transition metals (TMs) form, and thus on their lattice sites, deep levels can be created, forming recombination centers and, therefore, acting as lifetime killers for minority carriers 2,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation of metals via retrograde melting may also be applied to control the remaining dissolved species become supersaturated, and preferentially diffuse to existing defects to minimize interfacial and volume-change strain energy. [ 23 ] As the temperature drops to the liquidus, NiSi 2 begins to precipitate, migrating away from the homogeneous liquid droplets and forming nodules or separate precipitates. Due to the high diffusivity of nickel and copper at elevated temperatures, [ 14 ] signifi cant rearrangement of the particles is possible, as evidenced by the changing ratios of Cu and Ni in the bicolor coded μ -XRF maps in Figure 3 a .…”
mentioning
confidence: 99%